Neonatal exposure to a glyphosate-based herbicide alters uterine decidualization in rats - Ingaramo, Paola Inés (2017)
We investigated whether defective modulation of uterine signaling may cause decidualization failure in rats neonatally exposed to a glyphosate-based herbicide (GBH). Female pups received vehicle or 2 mg/kg of GBH from postnatal day (PND) 1 to PND7. On PND8 and PND21, Wnt5a and β-catenin expression was evaluated in uterine samples. On gestational day (GD) 9, Wnt5a, Wnt7a and β-catenin expression and Dkk1 and sFRP4 mRNA were evaluated on implantation sites. On PND8, GBH-exposed rats showed increased Wnt5a and β-catenin expression in luminal epithelium (LE), whereas on PND21, they showed increased Wnt5a and β-catenin expression in subepithelial stroma but decreased β-catenin expression in glandular epithelium. On GD9, GBH-exposed rats showed decreased Wnt5a and Wnt7a expression in the antimesometrial zone and LE respectively, without changes in β-catenin expression, while Dkk1 and sFRP4 were up- and down-regulated respectively. We concluded that neonatal GBH exposure may lead to embryo losses by disturbing uterine signaling.